Congestion control technique for mantes with neural networks - Sharma, Shikha; Kapoor, Er. Nitika (International Journal of Engineering and Technology, 2018)
The Mobile Ad hoc network is the network which is established for short duration of time and without central controller. Due to such unique properties of the network, quality of service is the major issue which affects network performance in terms of quality of service. The routing protocols are used for the path establishment from one end to another. The AODV is the most efficient reactive routing protocol for path establishment. In the AODV protocol, no counter measure is proposed yet for the congestion avoidance. The AODV protocol is modified in this research work for the congestion avoidance in the network. In the modified AODV protocol, the neural networks is applied for the error reduction in the network. The mobile node, which has least chances of error, is selected as best node for the data transmission. The proposed AODV protocol is implemented in NS2 and results are analyzed in terms of certain parameters. The proposed AODV protocol shows high performance than existing AODV protocol in terms of throughput and packet loss